Analisis Continuance Use IntentionAplikasi Access by KAI Menggunakan Expectation Confirmation Model - Sarip Hidayatuloh; Fazia Putri Handira (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
Continuance Use Intention refers to a condition in which users are satisfied with their experienceof using an information system, thereby encouraging them to continue using the system consistentlyin the future. Access by KAI is the official mobile application developed by PT Kereta ApiIndonesia (PT KAI) that provides online railway ticket booking services. However, the applicationhas experienced several challenges, including a decline in its user rating since its launch in 2023, arelatively low number of active users, and unresponsive customer support services. This study aimsto provide practical recommendations for improving the application based on an analysis using theExpectation Confirmation Model (ECM), particularly through enhancements to the application'suser interface (UI) and user experience (UX) design. The study adopts a modified ECM byincorporating four additional constructs: system quality, service quality, information quality, and habit. The research population consists of Access by KAI users residing in the Greater Jakartametropolitan area (Jabodetabek), with a sample of 400 respondents selected using purposivesampling. Data were analyzed using the Partial Least Squares–Structural Equation Modeling(PLS-SEM) approach implemented in SmartPLS 4. The findings indicate that continuance useintention is at a strong level, with an explanatory value of 0.733 (73%). Furthermore, perceivedusefulness, habit, and satisfaction were identified as significant determinants of continuance useintention. The proposed interface redesign is expected to serve as a practical implementation of thestudy's recommendations and assist PT KAI in prioritizing the development of application featuresthat better address users' needs and expectations